2006
DOI: 10.1007/s11249-006-9081-0
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids with ammonium cations as lubricants or additives

Abstract: A new class of more effective lubricants could lead to huge energy savings. Limited recent literature has suggested potential for using room-temperature ionic liquids as lubricants, however, only a few out of millions (or more) of species possible have been evaluated. In this study, a series of new protic alkylammonium ionic liquids were synthesized by neutralization and metathesis reactions, and have demonstrated promising lubricating properties as neat lubricants or lubricant additives, particularly for use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
228
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(248 citation statements)
references
References 17 publications
12
228
2
6
Order By: Relevance
“…Material pairs such as steel/steel, steel/SiO 2 , steel/aluminium, steel/copper, steel/Si(100), steel/sialon, steel/titanium, sialon/Si 3 N 4 and steel-PVD coatings (TiN, DLC and CrN) have been explored using pyridinium, imidazolium, phosphonium or ammonium as cation combined with anions such as hexafluorophosphate (PF 6 ), tetrafluoroborate (BF 4 ), CF 3 SO 3 , (C 2 F 5 ) 3 PF 3 (or FAP) and (CF 3 SO 2 ) 2 N (or NTf 2 ) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The most common anions examined in the tribology literature are BF 4 and PF 6 , but their hydrolytic instability and tendency to produce corrosive HF have been reported [27]. Merck KGaA has developed a new category of ILs using the FAP anion, which has an improved hydrolytic stability [28].…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Material pairs such as steel/steel, steel/SiO 2 , steel/aluminium, steel/copper, steel/Si(100), steel/sialon, steel/titanium, sialon/Si 3 N 4 and steel-PVD coatings (TiN, DLC and CrN) have been explored using pyridinium, imidazolium, phosphonium or ammonium as cation combined with anions such as hexafluorophosphate (PF 6 ), tetrafluoroborate (BF 4 ), CF 3 SO 3 , (C 2 F 5 ) 3 PF 3 (or FAP) and (CF 3 SO 2 ) 2 N (or NTf 2 ) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The most common anions examined in the tribology literature are BF 4 and PF 6 , but their hydrolytic instability and tendency to produce corrosive HF have been reported [27]. Merck KGaA has developed a new category of ILs using the FAP anion, which has an improved hydrolytic stability [28].…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…The friction and wear behaviour of ILs as additive or as pure lubricant have been studied using synthetic and mineral oils, or even fully formulated oils, as base oils or reference samples [27,[33][34][35] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 The additivation value of fully formulated oils with ILs needs further consideration and research.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…ILs are evolving from electrochemical and general solvents, 17,18 to novel materials in diverse applications such as specialized solvents, 19 lubricants, [20][21][22] thermal fluids, 23 magnetic fluids, [24][25][26] optical fluids, 27 propellants, 28,29 etc. Interdis- 36 Bioniqs, 37 etc.).…”
Section: Ionic Liquids As Technology Enablers and Novel Materialsmentioning
confidence: 99%
“…Since 2001, many studies have reported on the tribological properties of ionic liquids (ILs) as an additive in mineral and/or synthetic base oils [3,[6][7][8][9][10], and others on their use as engine lubricants [3,4,7,11,12]. ILs have some key inherent properties that make them suitable for an engine environment, such as high thermal stability, very low volatility, non-flammability, detergency in being a solvent, they are non-corrosive, have good wettability, and excellent tribological performances [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…ILs have some key inherent properties that make them suitable for an engine environment, such as high thermal stability, very low volatility, non-flammability, detergency in being a solvent, they are non-corrosive, have good wettability, and excellent tribological performances [3,7]. In this article, the authors present their recent experimental work on the assessment of boundary film forming behavior of two phosphonium-based ILs as additives in an engine-aged lubricant.…”
Section: Introductionmentioning
confidence: 99%